Factors influencing narrative construction of five-year-old children - Tan, Leif Daryl C.; Reyes, Clarissa F.; Corrales, Elija Grace Cantor (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The study explored the narrative construction of five-year-old children and the factors affecting it, such as interactions with household members, television viewing hours, number of years in school, and parent practices; from a purposive sampling of respondents from Quezon City, Cainta, Rizal and San Juan City. Thirty pairs of children and their parents were asked to retell a story, and were interviewed on the factors influencing narrative construction, respectively. Through descriptive statistics of the decile frequency table, narrative construction of children such as productivity, vocabulary, and grammar; and the qualitative analysis of parent responses on the factors affecting the child's narrative construction; results showed positive effect of number of household members and the parental practice of insisting the child to talk straight in sentences. Other factors showed to be either inconclusive or have affected the narrative construction negatively among the children in the sample.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Narrative construction